Better tracking SDG progress with fewer resources? A call for more innovative data uses - Hai-Anh Dang; Calogero Carletto; Dean Jolliffe (Global Labor Organization (GLO), 2024)
Existing data are severely insufficient for monitoring progress on the Sustainable Development Goals (SDGs), particularly for poorer countries. While we should continue efforts to produce new, high-quality data, this approach seems not feasible for all poorer countries. We call for a more systematic use of recent innovations with techniques such as data imputation to address existing data challenges. Given some resistance to utilizing new methods for filling data gaps, efforts aiming at changing the current perception and employing a mix of new data collection and data imputation can be useful. We also note that the best and most cost-effective approach would be highly context-specific and depends on various factors such as available budget, logistical capacity, and timeline.
Keywords: C15; I32; O15; 330; poverty; imputation; Sustainable Development Goals; developing countries